The Treaties of Karlowitz in the light of reports from the “Gazette de France” in 1699 - Ujma, Magdalena (Balcanica Posnaniensia. Acta et studia, 2003)
The article analyses how the peace treaties concluded in Karlowitz in 1699 were reported by the French newspaper „Gazette de France”. The background to the study is the significance of the Karlowitz treaties as a turning point in relations between the Christian powers and the Ottoman Empire, as well as the growing interest of Western European public opinion in political events in Central and Eastern Europe. The aim is to reconstruct the image of political events, diplomatic negotiations and the consequences of the peace treaty as presented by the French press. Particular attention was paid to the way in which the actions of the Polish-Lithuanian Commonwealth, Austria, Venice, Russia and the Ottoman Empire were presented. The primary source was a series of editions of „Gazette de France” from 1699, which published reports from Warsaw, Vienna, Venice and other European capitals. The research method is a comparative analysis of the press reports and historical facts known from other sources. This made possible to capture the differences in the narrative and to point out the propaganda nature of individual texts. The „Gazette” conveyed information in a concise and official manner, without in-depth interpretation. It emphasised the political and economic benefits of the peace treaty, but also pointed to the difficulties in its implementation – especially the delays in the evacuation of Kamieniec Podolski and tensions in relations with the Tatars and Turkey.